Achievement Analysis and Evaluation of a Hospital in Yogyakarta - Ahmad Ramadhan (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
The aim of this study is to evaluate hospital management indicator progress, analyzing the indicator and also described M Hospital management indicators. This study is using mix method design with explanatory sequential. Participants consist of the pharmacist, the head of the medical record unit, clinical risk management and patient safety committee, the head of a radiology unit, inpatient, permanent staff of the hospital, and the head of financial officer hospital management. Overall, the data showed that M Hospital’s indicator hasn’t completely matched it’s agreed on an element. Nine newly researched indicators were proposals from each unit. However, the indicator understudy remains relevant for measuring the needs of this hospital in order to improve the quality of patient care and safety.